New records of lichens and lichenicolous fungi from Eastern Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Five species of lichens and thirteen lichenicolous fungi are reported from the Eastern Ukraine. All species of the lichens and lichenicolous fungi were identified during studies conducted in the territory of the Kharkiv and Donetsk regions in 2012–2018, as well as during revision of materials from herbaria CWU and KHER. Calicium pinastri is a new for the plain part of Ukraine. It lignicolous species characterized by thin inconspicuous thallus, black stalked apothecia with brown hypothecium and 1-septate ellipsoid brown ascospore. Ten species of the lichens and lichenicolous fungi are new for the Left-Bank part of Ukraine. There are Clypeococcum hypocenomycis, Didymellopsis perigena, D. pulposi, Erythricium aurantiacum, Flavoplaca austrocitrina, Lichenochora hypanica, L. weillii, Marchandiomyces corallinus, Psorotichia montinii, Pyrenidium actinellum. Lichenodiplis lecanorae, Placopyrenium trachyticum and Scytinium tenuissimum are reported for the first time for the Left-Bank Forest Steppe of Ukraine. Athelia arachnoidea, Cercidospora macrospora, Codonmyces lecanorae and Lichenostigma elongatum are first time reported to Kharkiv region. The lichenicolous fungus Lichenochora hypanica characterized by black globous immersed pseudothecia up to 150 mkm diam., 2-4-spored asci and 1-septate hyaline narrowly ellipsoid ascospore. This is the first report of L. hypanica outside of a type locality. It specimen was found on thallus of Endocarpon pusillum which is the new host species. The localities in Ukraine, ecology and distribution data for the new records are provided. The Ukrainian descriptions of Calicium pinastri and Lichenochora hypanica are given. Currently, there are 17 species of lichenicolous species was reported in Kharkiv region.
Keywords: Calicium, Clypeococcum, Didymellopsis, Erythricium, Lichenochora, Pyrenidium, Psorotichia, Eastern Ukraine.